The affair. Season two [videorecording (DVD)] - West, Dominic, 1969-; Wilson, Ruth, 1982-; Tierney, Maura, 1965-; Jackson, Joshua, 1978- (Paramount, 2016)
With a murder unsolved and a betrayal exposed, the truth is suspect and shifting between the perspectives of Noah, Alison, Helen and Cole. The story now reveals the complex family ties, passionate betrayals and vengeful emotions that have resulted from the illicit summer liaison. And as the two estranged couples try individually to plan for the future, a new series of deceptions will once again force them to question everything they believed.